Bardet-biedl syndrome: A case report from Nepal - Mandal, Rajesh Kumar; Pande, Rajan; KC, Rajani Shah; Acharya, Bibek (Asian Journal of Medical Sciences, 2021)
The Bardet–Biedl syndrome (BBS) is a rare ciliopathic autosomal-recessive disorder, with multiple organ systems involvement. It is usually seen in family with consanguinous marriage. It is characterized by truncal obesity, polydactyly, retinal dystrophy, mental retardation, renal dysfunction and hypogonadism in males. It affects both males and females. Very few cases are reported in Nepal. Here we report a 30 year obese lady who presented to our center with history of excessive weight gain and blindness with polydactyly. She visited many local medical centers before landing to our hospital.